O mercado de luxo na China: da criação de uma classe capitalista chinesa ao consumo de luxo - Beirão, Dora Reolon (Universidade do Vale do Rio dos Sinos, 2022)
Within the International Relations, this research addresses the main characteristics of the luxury consumer market in China, from its formation to the current molds. Seeking to answer how the Chinese luxury market is presented, this study - using qualitative research tools - was able, throughout its five chapters, to illustrate the main characteristics of the luxury market, consumption and consumer of the Asian country. Currently, consumption is seen as a differentiating factor between individuals. Consuming, for some time, is no longer simply a pragmatic act aimed at the utility of the consumed object. Nowadays, in addition to consuming a good, its meanings and symbologies are consumed as well, aiming to satisfy personal desires and achieve prestigious images among different social groups. The luxury products and services market represents the epitome of this process, signaling status and distinction to its select and restricted group of consumers. The ode to opulence and ostentation are intrinsic factors in this universe, whose existence dates back to Ancient Egypt. Currently, the luxury market is mainly controlled by big names from the western industry, who are incessantly looking for new growth opportunities around the globe. In China, brands of this segment were faced with a long-repressed demand, due to political, social and economic ideals of the Maoist Era. With the structural reforms undertaken in 1978 in the country by Deng Xiaoping, named as the "Open Door Policy" - which made China's economic opening to foreign investment possible - a process began that enabled the accumulation of individual capital in China and the creation of a Chinese capitalist class. From this, with the increase of the purchasing power of the Chinese population, luxury brands began to seek a space in this market. The Chinese, whose appreciation for luxury items dates back to the Tang and Ming imperial dynasties, were able to reconnect with their culture and, with the mass entry of Western luxury brands in the country, began to claim greater representation of the culture in the products and an increase in the participation of Chinese designers and employees in the brands. Supported by its importance for the luxury industry, given that the consumer market for luxury products and services in China is - currently - the second largest in the world, the population begins to pressure the industry and, the consequences of this phenomenon, may leverage the prestige and recognition of Chinese culture on a global level. Assiduous luxury consumers, the Chinese could, in 2025, represent 40% of the world's total luxury consumption, making it the largest consumer market for luxury goods in the world, displacing the current first place, the United States.
Keywords: Consumo; Indústria de luxo; China; Classe capitalista chinesa; Mercado consumidor de luxo chinês; Consumption; Luxury industry; Chinese capitalist class; Chinese luxury consumer market